Inclusive Technology of Interaction between Specialists of Preschool Educational Institutions “Outside The Office” as an Effective Form of Psychological and Pedagogical Support for Children with Special Educational Needs - Akulova, E.G. (Bulletin of Practical Psychology of Education, 2020)
The article proposes practice-oriented innovative approaches to teaching children with special educational needs. The author describes the problems due to which the process of increasing the availability of quality education for these children is greatly complicated. He also offers a technology to solve these problems. It's essence is in the introduction of effective forms of work to prevent the "social exclusion" of these children. The proposed inclusive technology “Outside the Office” is part of the technological complex “Park of Inclusive Technologies: From Loneliness to People”, which became the winner of the “All-Russian Competition of the best psychological and pedagogical programs and technologies in the educational environment — 2019”. The testing of the inclusive technology “Outside the Office” was carried out for 4 years on the basis of the Kindergarten No. 13 of Tomsk. Methods were developed and put into practice for including children with special educational needs among their peers, as well as effective methods and techniques for working with narrow specialists and additional education teachers. The article claims that the basis of the inclusive technology “Outside the Office” is the cultural-historical concept of the development of mental functions of L.S. Vygotsky. The tasks, the participants of the inclusive process, the basic technological principles and the content of the inclusive technology “Outside the Office” are described. В статье предлагаются практико-ориентированные инновационные подходы к обучению детей с особыми образовательными потребностями. Автор описывает проблемы, из-за которых процесс повышение доступности качественного образования для этих детей сильно осложняется. А так-же предлагает технологию для решения этих проблем. Ее суть — внедрение эффективных форм работы по предотвращению «социальной исключенности» детей. Предлагаемая инклюзивная технология «За рамками кабинета» является частью технологического комплекса «Парк инклюзивных технологий: «От одиночества к людям», ставшего победителем Всероссийского конкурса лучших психолого-педагогических программ и технологий в образовательной среде — 2019. Апробация инклюзивной технологии «За рамками кабинета» проходила в течение 4-х лет на базе детского сада № 13 г. Томска. Были разработаны и введены в практику методы включения детей с особыми образовательными потребностями в среду сверстников, а также эффективные способы и приемы работы узких специалистов и педагогов дополнительного образования. В статье утверждается, что в основе инклюзивной технологии «За рамками кабинета» лежит культурно-историческая концепция развития психических функций Л.С. Выготского. Описываются задачи, участники инклюзивного процесса, основные технологические принципы и содержание инклюзивной технологии «За рамками кабинета».